Social relations and remittances: evidence from Canadian micro data - Don J. DeVoretz; Florin P. Vadean (Institute for the Study of Labor (IZA), 2006)
We theorise that remittances to persons outside the households represent transfers to maintain social relations with relatives and friends and charitable remittances are expenditures which foster group membership. We estimate transfer functions as part of a larger expenditure system and calculate Engel elasticities for remittances to persons and to charities. We conclude that expenditures to enhance social relations with relatives and friends are a normal good for recent Asian immigrants and a luxury good for all other immigrants and Canadians. This fact indicates strong cultural differences in the remittance behaviour of the population groups included.
urn:nbn:de:101:1-20080509134
Keywords: 330